Pattern of Admission, Management and In hospital Outcome of ACS Patients during COVID-19 pandemic - A study in Tertiary Care hospital (Bangladesh Heart Journal, 2022)
Aim: This study aimed to evaluate the impact of coronavirus disease2019(Covid-19) outbreak on admissions for acute coronary syndrome (ACS) and related mortality, severity of presentation, major cardiac complications, and outcome in tertiary care hospital (NICVD). Method: This is a cross sectional observational study on ACS admitted patients during the 1st and 2nd phase of COVID-19 from 1st June to 31st August in the year 2020 and 2021 who were COVID negative (RT PCR). Using a control of ACS admitted patients during corresponding period of year 2019 from registry. Results: During the 1st phase of COVID (July to August 2020) 736 ACS patients were enrolled where as during 2nd phase (July to August 2021) 722 ACS patients were enrolled. Mean age were 52±8 vs 53±11 years. Demographic variables such as age, sex and risk factors are almost identical in all groups. Our study showed 46% decline in admission in ACS patients comparing same period of 2019. Though some inclination in 2021 still it showed 13% decline in ACS patient admission in comparison to 2019. There was substantial increase in percentage of patient suffering from STEMI in 2020(42% vs66% vs46%). Short time in hospital complications were more pronounced in 2020. During the study period average death rate was higher than the year 2019 (8.6% vs 5.8%). There was significant decline in numbers of interventions(CAG and PCI) for CAD during first phase of Covid which raised during second phase(429 vs 2151). Total number of interventions done of 1884 patients in 2019 whereas 2151 patients were undergone in the year 2021. Conclusion: The Covid-19 outbreak affects hospital admission for acute coronary syndrome. During the first phase of the pandemic, significantly less patients with ACS admitted, but those admitted presented with a higher mortality, more complications and a worse short time outcome. Therefore ,our data indicate that Covid- 19 had relevant impact on non-infectious disease status, such as acute coronary syndrome.Bangladesh Heart Journal 2022; 37(1): 65-71